Artifacts Versus Nature Body A Wealth-Additive Scheme of Enterprise, Economics, and Nature Managing - Matsui, Masayuki (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book proposes a wealth-additive scheme of managing and maximizing (win-win and sharing) the marginal value (eco-entropy) of artifacts by humanizing the artifacts' enterprise and their economics with nature. This type of clockwork would be achieved on a base of the science of nature versus artifacts and the body of science in my Springer books since 2008. My books are advancing factory science, economics, and the science of artifacts and play their role in the sandwich theory and its pair-map microcosm of the 3D-type, toward the development of body science. Then, the wealth-additive goal of the "body" is not only similar to the marginal profit, GDP, and value in economics, but also means the marginal diversity (eco-entropy) and its wealth of economics versus reliability (sustainability) in the body of the world. The modern world, for example, is faced with deadlocked negotiations over the Sustainable Development Goals (SDGs) bodies at the United Nations. Thus, the forthcoming world of SDGs would be much better and more constructive at transforming traditional bodies of the 3M&I class (human, material, money, and information) as some nano (gene/therblig)-transformation toward eco-entropy(marginal value/diversity) on earth. This semi-visible world is traditionally limited to a molecular size and is too rough at the practical rig-level. Thus, any unsolved and invisible contradictions left behind on earth are subject to SDGs in the practical world. This approach proposes a visible method that could find and solve these contradictions (angles) by transforming the artifact's body, consisting of the 3M&I gene. The pair-map microcosm and its Matsui's M-equation have been designed mainly based on nature and science books on artifacts (in 2016 and 2019). Following these visible methods, our well-being subject might be able to make a breakthrough or make such unsolved contradictions or stalemates subside as any SDGs society of individuals in the near future. Finally, the book will explore and construct a new academic discipline involving 3M&I body science versus cybernetics. And, the study introduces validation cases of convenience stores, self-driving cars, and robotization (individualization) of artificial objects as the realization of the supply-demand system and the ideal form of artificial and natural bodies. Based on this perspective, the dialogue is conducted according to a creative structure of six parts, twelve chapters, and two appendices.
Introductory Nature versus Artifacts Theory -- A New Academic Discipline on Artifacts -- Wealth-additive Discipline at GDP versus SDG -- Economics Science and Hyperboloid Body -- Win-win and Sharing World of Economics Body -- Outline of Nature Versus Artifacts Body -- Economic and Knowledge Engine of Body -- Virtual GDP Engine of Carnot-like Type -- AI-digital Engine of Economic and Knowledge Type -- Ternary/Pair-Map of Nature versus Artifacts Body -- Sollen and Ternary sw/Pair-Map of Body -- DX like Ternary/ Pair-Map Microcosm -- Management Body Approach to Realization -- Humanized Robot of Digital Transformation Type -- Digital-like Scheme of Human Body Type -- Towards New Body and its Discipline -- Nano x Intangible Body and its Relativity -- e-Management: On-managerial Self-driving.
Keywords: Operations research; Production management; Schools of economics; Economics; Operations Research and Decision Theory; Operations Management; Heterodox Economics; Political Economy and Economic Systems